Chemically modified xanthan and gellan for preparation of biomaterials for ophthalmic applications. Issue 11 (30th October 2019) - Hamcerencu, Mihaela; Popa, Marcel; Riess, Gerard; Desbrieres, Jacques
Abstract: Gellan and xanthan are extracellular polysaccharides with very interesting rheological or gelling properties. They are esterified with acrylic acid, acryloyl chloride or maleic anhydride. Consequently, due to the presence of carbon double bonds, hydrogels are obtained using a grafting–crosslinking process with N ‐isopropylacrylamide and N ′‐bisacrylamide. Such hydrogels, due to the presence of poly( N ‐isopropylacrylamide), are thermosensitive and present drug release properties which can be adjusted through the reaction conditions. This concept was demonstrated for ophthalmic applications. © 2019 Society of Chemical Industry Abstract : The presence of carbon double bonds in modified polysaccharides allows the formation of hydrogels, using a grafting–crosslinking process that is suitable for ophthalmic applications.